Analysis of Compression Strength on Plastic Brick Material - Mislina Alif; Devendra Aulianur; Anhar Anhar (LPPM Politeknik Aceh Selatan, 2019)
Plastic waste has a negative impact on the environment, handling plastic waste by utilizing plastic waste and sand to make plastic bricks. This study aims to make plastic bricks, test the compressive strength of plastic bricks and determine the density. Making plastic stones using the experimental method, this method of experimenting with experience to prove themselves a statement that is learned. Maximum compressive strength test results in samples 1, 1 kg of plastic: 1 kg of sand = 141.42 kg/cm2. Sample 2, 1.15 kg plastic: 0.85 kg sand = 117.23 kg / cm2 and Sample 3, 0.85 kg plastic: 1.15 kg sand = 112.50 kg / cm2. Average mass weight sample 1 (1.25 kg) and the average lost weight of sample 1 (0.75 kg), average weight mass of sample 2 (1.39 kg) and lost average sample weight 2 (0.61 kg), mass average weight of sample 3 (1.3 kg) and loss of average sample weight 3 (0.7 kg) with total material used 2 kg. Based on the results of compressive strength tests, plastic bricks meet quality standards (SNI 15-2-94-1991). Thus this research can replace industrial products and maintain a healthy environment.